Pelatihan Mencuci Tangan yang Baik dan Benar - Diah Harmawati; Retno Wuri Sulistyowati (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The purpose of washing hands is to provide socialization to children so that children know how to wash their hands properly and correctly in children at Al Fatah Kindergarten Merauke. Children become better able to keep their hands clean. After socialization, children become adept at washing their hands properly and correctly using soap.